Seni Pertunjukan Sebagai Strategi Pencitraan Kota Studi Kasus Solo International Performing Arts (SIPA) - Teti Darlenis (Institut Seni Indonesia Surakarta, 2021)
This research takes the title “PERFORMANCE ARTS AS A CITY IMAGING STRATEGY;Solo International Performing Arts (SIPA) Case Study. “The aim of this research is to understand the function and meaning of performing arts outside of artistic and aesthetic interests.In the context of this research, performing arts function as a city image strategy with a case study on the implementation of Solo International Performing Arts (SIPA).It is hoped that the SIPA performance will be able to become a city branding in Surakarta, which can then have multiple impacts or many benefits.